Peningkatan Kemampuan Komunikasi Matematis Siswa Menggunakan Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) Berbantuan Teknik Scaffolding - Agus Subiyakto; Intan Sari Rufiana; Dwi Avita Nur Hidayah (Universitas PGRI Madiun, 2020)
The aim of this study is to describe the implementation of Two Stay Two Stray (TSTS) cooperative learning assisted by Scaffolding techniques. This study is also to determine students' mathematical communication skills and student learning outcomes after the implementation of Two Stay Two Stray (TSTS) cooperative learning assisted by Scaffolding techniques. This research was conducted in class VIIIC of SMPN 1 Siman at 2019/2020 academic year. The Classroom Action Research (CAR) design was carried out in 2 cycles, in which the data collection instruments were in the form of test questions and observation sheets. Based on the findings, there is an improvement in student learning outcomes from cycle 1 and cycle 2 after applying Two Stay Two Stray learning (TSTS) assisted by scaffolding techniques. Furthermore, the communication skills of students are also increased. Some points that must be considered in implementating this learning procedures are firstly, teachers must pay attention to the allocation of time provided for each step of learning in accordance with the Learning Implementation Plan. Secondly, the teacher must optimize his role as a facilitator in cooperative learning type Two Stay Two Stray (TSTS) through various scaffolding techniques. Some of the techniques given here can be adapted to other learning models and materials. The teacher needs to be more selective in choosing the right technique for optimalizing learning.